The role of national education in acquiring the concept of citizenship among primary school students from the point of view of male and female teachers (Journal of the College of Basic Education, 2022)
The current search targeted:1. Recognizing the role of national education in acquiring the concept of citizenship among primary school students from the point of view of male and female teachers2. Identifying the extent to which the goals of national education are achieved through teaching them.3. Identifying the differences between male and female teachers in acquiring the concept of citizenship among primary school students according to the gender variable (males-females).4. Identifying the differences between male and female teachers in acquiring the concept of citizenship among primary school students according to the educational attainment variable (Bachelor's - Institute).